Editorial: . - Kadankavil, K. T. (Journal of Dharma, 1979)
Study of religious traditions of men has certainly a long history. In the Christian West it had long been confined to seminaries and denominational schools. But of late it has come to be regarded as a matter of general interest throughout the academic world. Both large secular state universities and small private colleges arc starting centres to cater to the growing interest arising from religious questions.